The priority of the individual in cultural inheritance. Issue 3 (27th June 2014) - Davis, Taylor; Margolis, Eric
Abstract: Smaldino's proposed extension of the theory of cultural evolution embraces emergent group-level traits. We argue, instead, that group-level traits reduce to the traits of individuals, particularly when it comes to the question of how group-level traits are inherited or transmitted, and that this metaphysical fact is integral to the theory of cultural evolution.